2020
DOI: 10.1002/agg2.20027
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and economic impacts of cover crops in Texas rolling plains cotton

Abstract: Cover crops have been proposed as a resource that could enhance the effect of no‐till (NT) cropping systems. Crop yield limitations due to cover crops in the U.S. Great Plains are a concern to potential adopters. This research determined the impact of cover crops on crop yield and economic return compared with conventional practices in dryland systems of the Texas Rolling Plains. The study conducted at the Texas A&M AgriLife Chillicothe Research Station evaluated the following treatments: (a) conventional till… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…We also found out that using crimson clover can reduce the variation in cotton lint yield. However, crimson clover was not a good biomass producer in our dryland experiment (DeLaune & Bevers, 2017). This is consistent with previous research on other cash crops that legume cover crops did not reduce yield (Nielsen et al., 2016; Snapp & Surapur, 2018), but may increase yield variation (Ott & Hargrove, 1989).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…We also found out that using crimson clover can reduce the variation in cotton lint yield. However, crimson clover was not a good biomass producer in our dryland experiment (DeLaune & Bevers, 2017). This is consistent with previous research on other cash crops that legume cover crops did not reduce yield (Nielsen et al., 2016; Snapp & Surapur, 2018), but may increase yield variation (Ott & Hargrove, 1989).…”
Section: Resultsmentioning
confidence: 72%
“…This indicates that by planting crimson clover, producers experience less income volatility with more stable income flow, and thereby face a lower chance of observing extremely low or extremely high net returns. However, experimental results on cover crop performance, soil health and soil water content showed crimson clover had 50% less biomass and lower water use efficiency, compared to other cover crops (DeLaune, Mubvumba, & Lewis, 2016; DeLaune & Bevers, 2017). The net return to cotton producers who adopted no‐till with crimson clover ranged from $92 to $635 ha −1 , which was the narrowest range of net returns among all treatments.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(2017) reported no difference in soybean and corn yields following cover crops 1 to 2 yr after implementation. As several studies reported no significant lint yield reduction following cover crops under dryland conditions in the southern Great Plains (DeLaune et al, 2020; Segarra, Keeling, & Abernathy, 1991; Sij, Ott, Olson, Baughman, & Bordovsky, 2003), no yield reductions were expected under irrigated conditions as any deficit in stored soil moisture could be replaced by irrigation. Nouri, Lee, Yin, Tyler, and Saxton (2019) observed no significant difference in lint yields among a hairy vetch cover crop, wheat cover crop, and no cover crop (NT and CT) during years 33 and 34 of a 34‐yr Tennessee cotton cropping system.…”
Section: Resultsmentioning
confidence: 97%
“…Recent studies evaluating multispecies cover crops on agronomic production have shown mixed results (Chu et al., 2017; Finney, White, & Kaye, 2016; Smith, Atwood, & Warren, 2014; Wortman, Francis, Bernards, Drijber, & Lindquist, 2012). Within Texas cotton systems, research has shown no significant yield improvement due to a multispecies cover crop over a single species cover crop in irrigated (Lewis et al., 2018a) and dryland conditions (DeLaune, Mubvumba, Fan, & Bevers, 2020).…”
Section: Introductionmentioning
confidence: 99%